Family Diversity for Pre-School and Primary Education Teachers at Spanish Public Universities - Peregrina-Nievas, Paula; Caurcel-Cara, María Jesús; Cid-González, Christian; Crisol Moya, Emilio (Journal of Education Culture and Society, 2026)
Aim. This study analyses the training on family diversity received by future teachers in the Early Childhood Education and Primary Education Degrees in Spanish public universities. The study’s objectives were: 1) to analyse the training students receive in family diversity, 2) to understand how this topic is approached in Spanish universities, and 3) to evaluate whether this training is sufficient for inclusive teaching.Methods. Using content analysis methodology, forty study plans for the Early Childhood Education Degree and 39 for the Primary Education Degree from all Spanish public universities were reviewed, including basic, mandatory, and optional courses.Results. The results showed that, in general, the Early Childhood Education Degree addresses the topic more than the Primary Education Degree. Furthermore, the “family diversity” category barely has a presence.Conclusions. In conclusion, the training in family diversity in both degrees is insufficient to develop adequate inclusive teaching. The curricula do not truly address how to work with and manage the participation and inclusion of new family models. The focus is primarily on the family’s role in child development and the importance of the family-school relationship, without delving into current family models.